Lip Synechia Resulting From Toxic Epidermal Necrolysis: A Rare Condition - Mendes, Bruno Coelho [UNESP]; Santos, Anderson Maikon de Souza [UNESP]; Cervantes, Lara Cristina da Cunha [UNESP]; Pereira, Rodrigo dos Santos [UNESP]; Hochuli-Vieira, Eduardo [UNESP]; Bonardi, Joao Paulo (Lippincott Williams & Wilkins, 2020)
Toxic epidermal necrolyses represent a severe epidermolytic reaction characterized by cutaneous erythema and target lesions affecting >30% of the body surface, skin, and mucous membranes. Ulcerative lesions on the labial mucosa may evolve during healing, resulting in rare complications, such as lip adhesions. This report shows the successful treatment of a lip synechia resulting from the healing of mucosal lesions in a patient with toxic epidermal necrolysis caused by the use of Lamotrigine and Ibuprofen. Although the treatment of the presented lip synechia was simple, this sequela can be avoided by measures such as hydration, hygiene and lip lubrication.
Keywords: Surgery; tissue adhesions; toxic epidermal necrolysis